The development of a concept of psychological well-being - Bar-On, Reuven (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
This thesis focuses on the development of an operational and theoretically eclectic concept of psychological well-being. A comprehensive research strategy was employed to examine various personality factors thought to be components of psychological health (i.e., the basis of the proposed concept). The general approach involved four major phases: (1) the clustering of various variables and identification of underlying key factors purported to be related to psychological health based on the writer's clinical experience and review of the mental health literature, (2) the formulation of an ~ priori concept of psychological well-being based on the operational definition of those factors, (3) the construction of an inventory designed to examine the proposed concept, and (4) the interpretation of the results and their implications for the development of the overall concept based on the examination of the factorial structure, validity and reliability of the inventory. The"a posteriori concept" evolved out of this process. The results of the present study indicate that the most valid and reliable factorial components of psychological well-being are self regard,interpersonal relationship, independence, problem-solving, assertiveness,reality testing, stress tolerance, self-actualization and happiness; social responsibility and flexibility emerged as questionable components of the a posteriori concept. The inventory which was designed to study the concept was successful in significantly differentiating various levels of psychological health. This way of conceptualizing and assessing psychological well-being has potential applicability for mental health practitioners and researchers.
Keywords: Mental health -- Psychological aspects; Personality